2013
DOI: 10.1095/biolreprod.113.109728
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Regulation of AMP-Activated Protein Kinase (AMPK) in the Pacific Oyster Crassostrea gigas1

Abstract: The hermaphrodite Pacific oyster Crassostrea gigas displays a high energy allocation to reproduction. We studied the expression of AMP-activated protein kinase (AMPK) during gametogenesis in the gonad and characterized the mRNA sequences of the AMPK subunits: the AMPK alpha mRNA sequence was previously characterized; we identified AMPK beta, AMPK gamma, and mRNAs of putative AMPK-related targets following bioinformatics mining on existing genomic resources. We analyzed the mRNA expression of the AMPK alpha, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 119 publications
2
24
0
1
Order By: Relevance
“…However, the current results showed that CLA induced AMPKα activation only in female flies. This type of sex‐specific regulation of AMPKα was previously observed in other organisms with differing energy abundance and utilization between sexes (Guevelou et al, ; Zawada et al, ). It is also possible that the increase of locomotor activity by CLA in males may be associated with carbohydrate metabolism (decrease in akh ) and/or courtship behavior, independent of AMPKα.…”
Section: Discussionsupporting
confidence: 72%
“…However, the current results showed that CLA induced AMPKα activation only in female flies. This type of sex‐specific regulation of AMPKα was previously observed in other organisms with differing energy abundance and utilization between sexes (Guevelou et al, ; Zawada et al, ). It is also possible that the increase of locomotor activity by CLA in males may be associated with carbohydrate metabolism (decrease in akh ) and/or courtship behavior, independent of AMPKα.…”
Section: Discussionsupporting
confidence: 72%
“…Samples were weighted and homogenized in a Tris‐HCl buffer (pH 7.4) as described in Guévélou et al. (). Total protein extraction was performed using an Ultra‐Turax (Kinematica Kriens‐Lu) in an ice‐bath followed by a centrifugation at 15000 g during 20 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Relationships between metabolism and fertility are well established, particularly in the female. Recent discoveries show that AMPK is also present in male gonad and spermatozoa in different species [Caenorhabditis elegans (Lee et al, 2008), oyster (Guevelou et al, 2013), chicken (Nguyen et al, 2014), boar (Hurtado de Llera et al, 2012, 2013), mouse (Tanwar et al, 2012; Tartarin et al, 2012), stallion (Cordova et al, 2014), and human Calle-Guisado et al, 2016; Shabani Nashtaei et al, 2016]. It is these roles in male gonad and spermatozoa that I will now describe.…”
Section: Structure and Expression Of Ampkmentioning
confidence: 99%
“…The links between differences in subcellular localization of AMPK and spermatozoa biological characteristics of different species, however, have not yet been defined. In invertebrates, AMPK has also been highlighted in 2013 in oyster's male and female germ cells, where it is involved in the glucose and fatty acids metabolism (Guevelou et al, 2013). …”
Section: Role Of Ampk In Male Gonad and Sperm Productionmentioning
confidence: 99%